Mussolini the rise and fall of Il Duce - Hibbert, Christopher (New York Palgrave Macmillan, 2008)
With his signature insight and compelling style, Christopher Hibbert explains the extraordinary complexities and contradictions that characterized Benito Mussolini. Mussolini was born on a Sunday afternoon in 1883 in a village in central Italy. On a Saturday afternoon in 1945 he was shot by Communist partisans on the shores of Lake Como. In the sixty-two years in between those two fateful afternoons Mussolini lived one of the most dramatic lives in modern history. Hibbert traces Mussolini's unstoppable rise to power and details the nuances of his facist ideology. This book examines Mussolini's legacy and reveals why he continues to be both revered and reviled by the Italian people.
Includes bibliographical references (p. [346]-355) and index.
Keywords: Mussolini, Benito, 1883-1945.